+0  
 
0
118
1
avatar

If $x-y=6$ and $x^2+y^2=24$, find $x^3-y^3$.

Guest May 13, 2018
 #1
avatar+963 
+2

Hi Guest!

 

We use: \(x^3-y^3=(x-y)(x^2+xy+y^2) \)

 

We already know \( (x-y)\) and \(x^2+y^2\)

 

We can plug the known values in, and we get:

 

\(6(24+xy)=x^3-y^3\)

 

To solve for xy, we use: \((x-y)^2=x^2-2xy+y^2\)

 

This means that \(6^2=24-2xy\)

 

Solving for xy, we get:

 

\(36=24-2xy\\ 12=-2xy\\ xy=-6\)

 

Now we can plug this into the original expression:
\(6(24-6)=x^3-y^3\\ x^3-y^3=108\)

 

I hope this helped,

 

Gavin

GYanggg  May 13, 2018

32 Online Users

avatar
avatar
avatar
avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.